Root cause study of corrosion stiction by brake pads on the grey iron disc. (October 2021) - Gweon, Jaehyun; Park, Jongsung; Lee, Wan Kyu; Kim, Doo Yeon; Jang, Ho
Highlights: Stiction force was affected by hydrophobicity and strength of brake pads. Stiction force changed mainly with pad surface strength and resultant contact area. Polarization resistance of corroded surfaces was proportional to the stiction force. Fe ions in the electrolyte oxidized and produced oxide layers on the pad surface. Abstract: Corrosion stiction at the sliding interface of a brake system was investigated to identify its leading cause and countermeasure. Porosity, acidity, hydrophobicity, strength, contact stiffness, and contact area of commercial brake pads were examined to find the correlation with corrosion stiction. Results showed that the compliant brake pads with low cohesive strength showed high stiction forces owing to the larger contact area after brake applications than stiff pads. Electrochemical analysis of the corroded interface supports the contact area dependency of the stiction force, suggesting that corrosion stiction can be reduced by minimizing the contacts on the brake pad surface.